IMPLEMENTASI APLIKASI E-LEARNING PADA PUSAT KEGIATAN BELAJAR MASYARAKAT - Abeputra Sihombing, Redo; Ryan Fernandes, Gilang; Mei Lina, Ika (COVIT (Community Service of Tambusai), 2021)
The development of Information and Communication Technology (ICT) is currently growing very rapidly. In the world of education, various kinds of services are now available that support technological developments. In educational institutions, one indicator of success is the application of Information and Communication Technology (ICT), which is now a must. One of the technologies that exist in the world of education, namely one of the e-learning systems. Some of the problems that often arise are in the delivery of learning content. Teachers experience difficulties in delivering or distributing material to students in PKBM. The purpose of this community service is the implementation of e-learning applications to help and be able to simplify and speed up the teaching and learning process at Community College PKBM. This community service activity uses presentation methods, lectures, discussions or a combination of these methods. This e-learning application uses the open source Moodle application. Keywords: E-Learning, Open Source, PKBM, Moodle